110k views
3 votes
Find the inverse transform by convolution: 4 (s-3)(s-2) C.27.

1 Answer

4 votes

I suppose you're asking about the inverse Laplace transform of


F(s)=\frac4{(s-3)(s-2)}

by way of the convolution theorem.

The theorem itself says that


\mathscr L^(-1)\{A(s)B(s)\}=(a*b)(t)

where
A(s) and
B(s) are the Laplace transforms of
a(t) and
b(t), respectively.

Let
A(s)=\frac1{s-3} and
B(s)=\frac1{s-2}. Then


a(t)=\mathscr L^(-1)\left\{\frac1{s-3}\right\}=e^(3t)


b(t)=\mathscr L^(-1)\left\{\frac1{s-2}\right\}=e^(2t)

So we have


\mathscr L^(-1)\left\{\frac4{(s-3)(s-2)}\right\}=e^(3t)*e^(2t)

Convolution is defined as


(a*b)(t)=\displaystyle\int_0^t a(t-\tau)b(\tau)\,\mathrm d\tau

The convolution of
e^(3t) and
e^(2t) is


e^(3t)*e^(2t)=\displaystyle\int_0^t e^(3(t-\tau))e^(2\tau)\,\mathrm d\tau


=\displaystyle e^(3t) \int_0^t e^(-\tau)\,\mathrm d\tau


=e^(3t)(1-e^(-t))=e^(3t)-e^(2t)

We end up with


\mathscr L^(-1)\left\{\frac4{(s-3)(s-2)}\right\}=\boxed{4(e^(3t)-e^(2t))}

User Igor Kostin
by
6.0k points